Bone biology‐related gingival transcriptome in ageing and periodontitis in non‐human primates. (6th April 2016) - Pandruvada, Subramanya N.; Gonzalez, Octavio A.; Kirakodu, Sreenatha; Gudhimella, Sudha; Stromberg, Arnold J.; Ebersole, Jeffrey L.; Orraca, Luis; Gonzalez‐Martinez, Janis; Novak, Michael J.; Huja, Sarandeep S.
Abstract: Aim: Cellular and molecular immunoinflammatory changes in gingival tissues drive alveolar bone loss in periodontitis. Since ageing is a risk factor for periodontitis, we sought to identify age‐related gingival transcriptome changes associated with bone metabolism in both healthy and in naturally occurring periodontitis. Materials and Methods: Adult (12–16 years) and aged (18–23 years) non‐human primates ( M. mulatta ) ( n  = 24) were grouped into healthy and periodontitis. Gingival tissue samples were obtained and subjected to microarray analysis using the Gene Chip Macaque Genome Array. Gene expression profiles involved in osteoclast/osteoblast proliferation, adhesion and function were evaluated and compared across and between the age groups. QPCR was also performed on selected genes to validate microarray data. Results: Healthy aged tissues showed a gene profile expression that suggest enhancement of osteoclastic adhesion, proliferation/survival and function (SPP1, TLR4, MMP8 and TFEC) and impaired osteoblastic activity (SMEK3P and SMAD5). The gingival transcriptome in both adult and aged animals with naturally occurring periodontitis (FOS, IL6, TLR4, MMP9, MMP10 and SPP1 genes) was consistent with a local inflammatory response driving towards bone/connective tissue destruction. Conclusion: A pro‐osteoclastogenic gingival transcriptome is associated with periodontitis irrespective of age; however; a greater bone‐destructive molecular environment is associated with ageing in healthy tissues.